2018
DOI: 10.1038/s41419-018-0588-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic patterns in insulin-sensitive male hypogonadism

Abstract: Male hypogonadism is a disorder characterised by low levels of the hormone testosterone. At beginning subjects with low levels of testosterone do not show insulin resistance (insulin-sensitive patients), which develops over time (insulin-resistance patients). To analyse the metabolic alterations mainly related to decreased testosterone, we performed metabolomics investigations on the plasma of males with hypogonadism who showed normal insulin levels. Plasma from patients with low testosterone (<8 nmol/l) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 34 publications
6
26
1
Order By: Relevance
“…Most of the AA changes in the present study were observed in previous studies on hypogonadism or T related disease as well as DM2 [9,19,20]. Notably, Tyr was reported significantly up regulated in hypogonadal males versus controls, while both Tyr and Phe were among the best risk predictors of developing DM2 [19].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Most of the AA changes in the present study were observed in previous studies on hypogonadism or T related disease as well as DM2 [9,19,20]. Notably, Tyr was reported significantly up regulated in hypogonadal males versus controls, while both Tyr and Phe were among the best risk predictors of developing DM2 [19].…”
Section: Discussionsupporting
confidence: 77%
“…Testosterone (T) has a highly complex metabolic effect on the major tissues involved in insulin action, such as the liver, fat and muscle tissues [2,9,10]. Research suggests that long-term T deficiency causes metabolic changes, such as favoring net protein breakdown resulting in decreased muscle mass.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the gene is regulated by hepatocyte-specific and liver-enriched transcription factors, as well as by hormones (24). Tyrosine has previously been reported to be upregulated in hypogonadal men and both tyrosine and phenylalanine levels were suggested as predictors of the risk of developing diabetes many years before manifest disease (43)(44)(45). In male tyrosine hydroxylase knock-out mice normal body weight, puberty onset, and basal gonadotropin levels in adulthood were evident, although T was significantly elevated in adult mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…To explore the age‐, BMI‐, and sex‐relevant metabolic functions and pathways for understanding the biological meaning of the observed metabolic changes, a metabolite pathway enrichment analysis was conducted using the widely applied MetaboAnalyst 4.0 web tool (Xia et al, 2015). Human species and hypergeometric test were selected as parameters for the pathway analysis and the threshold of FDR was set at 0.05 for allowing the research discovery (Fanelli et al, 2018).…”
Section: Methodsmentioning
confidence: 99%